2015
DOI: 10.1097/prs.0000000000001047
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Congenital Hand Differences

Abstract: Purpose Although functional outcomes following reconstruction for congenital hand differences are frequently described, much less is known regarding children’s ability to cope with psychosocial effects of these conditions. We qualitatively explored stress and coping mechanisms among children following reconstructive surgery for congenital hand differences. Methods Forty patients and their parents participated in semi-structured interviews examining stress related to hand functioning and appearance, emotional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 22 publications
4
52
0
Order By: Relevance
“…Studies show that children with persistent conditions develop coping strategies or “survivor sense” that could ultimately increase their SDet [19,28‐30]. During daily activities, children with NBPP might encounter physical challenges, and these challenges could cause frustration, stress, or even social difficulties [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies show that children with persistent conditions develop coping strategies or “survivor sense” that could ultimately increase their SDet [19,28‐30]. During daily activities, children with NBPP might encounter physical challenges, and these challenges could cause frustration, stress, or even social difficulties [19].…”
Section: Discussionmentioning
confidence: 99%
“…During daily activities, children with NBPP might encounter physical challenges, and these challenges could cause frustration, stress, or even social difficulties [19]. Coping strategies, such as social support or the recognition from peers or parents, could mediate the psychosocial impact of their physical impairment [29]. In a similar study that investigated self‐concept in youth with NBPP, the authors report that a greater level of social support is associated with better self‐concept and fewer social difficulties [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychosocial function is highly relevant for children with CHD [42,81]. In fact, Franzblau et al [30] found that 58% of children and 40% of parents reported stress related to their CHD. The authors found that 58% of this stress resulted from social interactions, 46% resulted from emotional reactions, and 27% resulted from hand appearance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, children and their parents invariably experience considerable psychological stress from the appearance of the involved limb. Previous studies demonstrate that parents of children with CHD frequently mourn the loss of their expectations for their unborn child, and children with CHD have difficulty coping with the functional and aesthetic manifestations of these conditions [12,30]. In this context, patient-and parent-reported outcome measures (PROMs) that can accurately and efficiently capture these experiences could provide important insight into the effect of CHDs on a child's psychosocial functioning and development.…”
Section: Introductionmentioning
confidence: 99%